2013
DOI: 10.1159/000354464
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Mediates AMPK-Dependent Autophagic Cytoprotection in H9c2 Cells During Hypoxia/Reoxygenation Injury

Abstract: Background: Acetylcholine (ACh), a neurotransmitter of vagal nerve, offers tolerance to ischemia/reperfusion injury. Given the regulation of autophagy in cardioprotection, this study was to examine the role of autophagy in ACh-elicited protection against hypoxia/reoxygenation (HR) injury. Methods: H9c2 cells were subjected to HR injury. Autophagy was determined by transmission electron microscopy, MDC staining and western blot. MTT kit, LDH and CK release, ATP content and TUNEL assay were used to evaluate card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 44 publications
6
74
0
Order By: Relevance
“…8-OHdG is a sensitive and specific marker of DNA damage induced by oxidative stress [30]. These findings are consistent with a previous report showing that myocyte autophagy was decreased during hypoxia and reoxygenization [31] in association with increased oxidative stress. Reduced myocyte autophagy also occurs in pressure overload-induced myocardial hypertrophy [3,25,26] and aging [32], all of which are associated with increased myocardial oxidative stress [33,34].…”
Section: Mechanisms Of Reduced Myocyte Autophagy After MIsupporting
confidence: 90%
“…8-OHdG is a sensitive and specific marker of DNA damage induced by oxidative stress [30]. These findings are consistent with a previous report showing that myocyte autophagy was decreased during hypoxia and reoxygenization [31] in association with increased oxidative stress. Reduced myocyte autophagy also occurs in pressure overload-induced myocardial hypertrophy [3,25,26] and aging [32], all of which are associated with increased myocardial oxidative stress [33,34].…”
Section: Mechanisms Of Reduced Myocyte Autophagy After MIsupporting
confidence: 90%
“…In a Langendorff model of ischemia/reperfusion, inhibition of autophagy with the cell-permeable inhibitor (TATAtg5K130R) neither increased nor reduced infarct size, suggesting that in the absence of pre-or post-conditioning, the beneficial and deleterious effects of autophagy may be balanced (34). Inhibition of autophagic flux increases hypoxia/ reoxygenation injury (109) and blocks the beneficial effects of sevoflurane postconditioning (107). Ischemia/reperfusion injury disrupts autophagosome-lysosome fusion (54), accompanied by a significant increase in Beclin-1.…”
Section: Ischemia-reperfusion: An Energy Supply Crisismentioning
confidence: 99%
“…Furthermore, a previous study from our laboratory showed ACh promotes cell survival via an AMPK‐induced cardiomyocyte autophagy pathway during cardiomyocyte hypoxia/reoxygenation injury 13. Increasing evidence suggests AMPK acts as a hub to bridge mitochondrial dysfunction and IHD 25, 26; however, AMPK's role in mitochondrial dynamics regulation during myocardial ischaemia remains unknown.…”
Section: Introductionmentioning
confidence: 96%